Evaluation on computer requirements for senior citizens - Sharanjit, Kaur (2013)
Negligence when comes to computer technology usage is considered a common problem faced by the senior citizens community. The study identifies some common difficulties while using computer and identifies the most popular computer technologies used among this community. Survey conducted with the targeted community where main issues were identified as requirements and opportunity of sharing knowledge among this community. Findings shows that specific computer technology requirement and suitable content of a web portal that suits senior citizens is essential so that the older generation who see computers and new technology as what they have the potential to be - a tool for expanding their horizons, learning new skills and finding new interests. For future research, study on the content of a web portal and the design guidelines analysis for the portal is suggested. This paper examines a proposed knowledge sharing portal features to get it adapted for this community.